Analysis of Prenatal Breastfeeding Self-Efficacy and Anxiety Surrounding Giving Birth During COVID-19 Among Pregnant Women in the United States. (7th June 2021) - McKinley, Erin
Abstract: Objectives: To assess the relationship between perceived level of anxiety and concern with giving birth during COVID-19 and level of prenatal breastfeeding self-efficacy among a sample of pregnant persons in the United States. Methods: A sample of 849 pregnant persons, representing all 50 states and 5 US territories, were recruited via social media advertisements to take a 78-item web-based survey between May and December of 2020. The survey items assessed prenatal breastfeeding self-efficacy using the valid PREP to BF scale, breastfeeding intention, anxiety with giving birth during COVID-19, concern for the baby being exposed at birth, and confusion with pregnancy recommendations during COVID-19. Results: The sample, mean age 28.9 years, had a relatively high mean PREP to BF score (308.52 ± 62.74; range 39–390). Over 95% indicated a plan to incorporate breastmilk into their infant feeding routine either exclusively (68.96%) or in combination (26.5%). Seventy-one % were not confused by safe pregnancy recommendations, while 50.7% were "concerned" or "very concerned" their baby would be exposed to COVID-19 at birth, and 63.3% indicated they were "anxious" or "very anxious" about giving birth during the pandemic. One-way ANOVAs revealed persons with higher perceived anxiety ( P  = .024), more confusion over recommendations ( P  < .001), and more concern for their baby's exposure ( P  = .002) had significantly lower PREP to BF scores than their counterparts. Conclusions: A pregnant person's anxiety, confusion over recommendations, and concern for their baby's safety had significant negative effects on prenatal self-efficacy for successful breastfeeding after birth during COVID-19. Prenatal healthcare teams should aim to discuss these aspects and reassure of proven safety protocols with pregnant patients to ease anxiety, confusion, or fear while helping to maintain or improve self-efficacy for the intended infant feeding method. Funding Sources: This material is based upon work supported by the National Institute of Food and Agriculture, US Department of Agriculture, Hatch project LAB94426.